Editorial Vol.1(2) - Mathema, Suraj R.B. (Journal of Nepalese Prosthodontic Society, 2018)
Journal of Nepalese Prosthodontic Society (JNPS) editorial team proudly present the second issue of JNPS after the successful publication of first issue. We hope that our team had been able to open a new chapter in the history of Nepalese Prosthodontic Society (NPS). We are expecting to get similar support and encouragement from the new executive committee in the coming days.First issue of JNPS covered the scientific papers ranging from research activities, review articles, innovative clinical and laboratory procedures and recent advances in material sciences and technology. We hope that it served the purpose of fostering knowledge and enhancing skill among academicians, clinicians and researchers alike.Second issue of JNPS also tries to covers the wide variety of scientific papers. We would like to thank all the authors, reviewers, editors and contributors associated with this journal for their relentless eff ort to publish this issue. We would also like to thank all the readers and well-wishers for their valuable comments and suggestions for upgrading the quality of JNPS. We welcome your comments and suggestions in forthcoming issues too.As editor-in-chief, I would like to thank all the editorial team of JNPS, executive committee and members of NPS, publication house and other persons, associated directly or indirectly, for their hard work, support and constant encouragement during the process of publication.